2009
DOI: 10.2174/1876396000902010016
|View full text |Cite
|
Sign up to set email alerts
|

Relative Bioavailability of Zinc in Yogurt Using Body Weight Gain, Femur Weight and Bone Zinc Content in Rats as Markers

Abstract: Abstract:Objective: some previous works have shown the importance of zinc in nutrition, and even evaluated different zinc sources for food supplementation with this micronutrient. The aim of this work was to evaluate zinc gluconate stabilized with glycine (BZ) as a zinc source for food fortification by employing yogurt as the vehicle and zinc sulfate (SZ) as the standard zinc source. Materials and methods: weaned Sprague Dawley rats were separated in 7 groups of 10 rats each, which were fed with diets accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…Mineral deposits evaluated as zinc and calcium bone content and as zinc and iron liver content, were comparable with those reported by other authors [23][24][25] and confirmed the results mentioned above. The mineral sources under study behaved like the reference standards in terms of the organ weight or the organ mineral content.…”
Section: Discussionsupporting
confidence: 92%
“…Mineral deposits evaluated as zinc and calcium bone content and as zinc and iron liver content, were comparable with those reported by other authors [23][24][25] and confirmed the results mentioned above. The mineral sources under study behaved like the reference standards in terms of the organ weight or the organ mineral content.…”
Section: Discussionsupporting
confidence: 92%
“…Diets for bioavailability assay were prepared based on a protocol previously described by others [26][27][28][29] and used in our laboratory [30,31]. Briefly, diets were prepared according to AIN-93G but modified in their zinc content and provision [32].…”
Section: Dietsmentioning
confidence: 99%
“…Groups CI, CII and CIII were fed diets containing zinc sulfate at 6 ppm, 18 ppm and 35 ppm, respectively, provided in the same vehicle without probiotic. The 10 th group was fed with a diet based on AIN -93G without zinc addition (2ppm) [31].…”
Section: Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fermentation is an advised process for reducing the level of phytate in food, by the activation of the endogenous native phytases and production of microbial phytase, which degrades phytates by the successive removal of the phosphate groups, resulting in an increased mineral bioavailability ( 3 , 12 , 13 ). There are studies showing the increased mineral bioavailability in fermented food in vitro ( 14 , 15 ) and a few in vivo studies in rats fed fermented food ( 16 ). However, to our knowledge, in vivo studies of mineral bioavailability in rats fed plant-based diets containing fermented food are still limited.…”
mentioning
confidence: 99%